Evaluación del impacto económico de los microcréditos otorgados por la cooperativa de ahorro y crédito Fernando Daquilema Ltda. oficina matriz, periodo 2018 - Unach (2019)
This study evaluated the economic impact of the microcredits granted by the Head Office of the Cooperativa de Ahorro y Crédito Fernando Daquilema Ltda., during the period 2018. The work sought to determine, through a comparative statistical analysis between new members (who maintain a single credit operation) and old members (with two or more credits), the impact that the microcredits granted by the institution have had on the economy of the beneficiary members. The results obtained show the partners with two or more credits have better economic indicators. To verify the objectives, a survey form was prepared for the leading group (former members) and for the control group (parners with a single credit) that allowed, first, to find the characteristics of the beneficiaries of the microcredit and second, obtain the necessary information to measure the economic impact of the microcredit beneficiaries. The work is structured as follows: Section I, it contains the introduction and approach of the problem; in section II, there are the general and specific objectives of the research. In section III, it has the theoretical foundation of the research, starting from an analysis of the state of the art, continuing with the theoretical foundation of the main variables of study and ending with the legal environment that governs cooperativism in Ecuador. The methodology for research, analysis and discussion of the results can be found in section IV. Finally, in section V, the conclusions and recommendations of the research work can be observed.